The The Use of WhatsApp Group to Maintain Intercultural Friendship - Ade Tuti Turistiati (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
This research aims to analyze the use of WhatsApp Group (WAG) as a medium for maintaining intercultural friendship among people with different cultural backgrounds namely the alumni of The Ship for Southeast Asian and Japanese Youth Program (SSEAYP) batch ‘89. This research used a case study approach with a qualitative research design. The data were collected through direct observation of the texts, pictures, emoticons, and videos shared in the WAG and interviews with 20 informants who are the members of the group coming from different countries. The Needs Hierarchy Theory of Maslow and the Social Exchange Theory of Thibaut and Kelley were used in this research. The findings show that the alumni of SSEAYP Batch ’89 joined the WAG to maintain intercultural friendship among them by exchanging information about their and their families’ conditions; expressing birthday wishes; congratulating each other’s achievements of studies or works; congratulating religious celebrations; fundraising for certain events; and coordinating reunions. To maintain their friendship, the WAG members implicitly agreed to an unwritten rule that they must respect each other, be tolerant, and be open-minded. They also agreed that topics related to politics and religion are not allowed to be posted and discussed in the group, except for greetings on religious occasions. In addition, humor that causes unnecessary laughter and pictures and videos that tend to be pornographic or demeaning to women should not be posted in the group. The discussion about football also should not be too deep to avoid fanaticism with certain teams or players which might result in division or enmity between the group members.